2006
DOI: 10.1002/jgm.914
|View full text |Cite
|
Sign up to set email alerts
|

Dual agent chemoprotection by retroviral co‐expression of either MDR1 or MRP1 with the P140K mutant of O6‐methylguanine‐DNA‐methyl transferase

Abstract: Tumour resistance to chemotherapeutic agents results in most chemotherapy being administered in a multi-agent fashion that is often associated with a high level of toxicity in highly proliferative tissues such as the haematopoietic compartment. Thus, whilst many genetic manipulation strategies aim to protect normal tissue against a single component of a multi-agent regime, it is clearly preferable to protect normal cells against all toxicities. In this study we have used retroviral gene transfer to achieve co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…33,55 Especially for MGMT, it was shown that the IRES-dependent expression in a retroviral vector resulted only in a tenth of active protein compared with CAP-dependent expression. 27 A high expression rate of the MGMT protein is important for efficient dealkylation of O 6 -guanines as each MGMT molecule is irreversibly inactivated after binding of one alkyl group. 8 The transgene itself might influence the IRES-dependent translation owing to its structure or sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,55 Especially for MGMT, it was shown that the IRES-dependent expression in a retroviral vector resulted only in a tenth of active protein compared with CAP-dependent expression. 27 A high expression rate of the MGMT protein is important for efficient dealkylation of O 6 -guanines as each MGMT molecule is irreversibly inactivated after binding of one alkyl group. 8 The transgene itself might influence the IRES-dependent translation owing to its structure or sequence.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Simultaneous gammaretroviral transfer of both resistance genes was performed only in vitro into cell lines or primary hematopoietic cells to assay for chemoprotection against various combinations of certain MDR1 substrate drugs with alkylating agents. [27][28][29][30] However, we showed for the first time efficient chemoprotection of HSCs using a third-generation lentiviral SIN vector for transfer of MDR1 and the MGMT P140K mutant. 31 This special form of MGMT is resistant against O 6 -benzylguanine (O 6 -BG), 32 an inhibitor of wild-type MGMT, which can be applied to block MGMT activity in tumor cells rendering them sensitive for an alkylating agent while HSCs expressing the mutant form are efficiently protected.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic chemoprotection of hematopoietic and progenitor stem cells with mutant AGT has been explored (Southgate et al, 2006). However, this approach does not consider extra-hematopoietic toxicities, and it needs to be optimized before any clinical application can be envisioned.…”
Section: Discussionmentioning
confidence: 99%
“…MDR1 and mutant MGMT have been integrated into one bicistronic vector to provide modified cells with protection against BG/ACNU or BG/TMZ and vincristine or paclitaxel treatments [27,74,75]. MDR1 and mutant MGMT have been integrated into one bicistronic vector to provide modified cells with protection against BG/ACNU or BG/TMZ and vincristine or paclitaxel treatments [27,74,75].…”
Section: Multidrug-resistant Gene (Mdr)mentioning
confidence: 99%